KARAKTERISTIK GURU PERSPEKTIF M. QURAISH SHIHAB DALAM TAFSIR AL-MISBAH - Ahmad Sulaiman (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2017)
Abstract: The purpose of this research is to know: (1). Characteristics of teacher perspective M. QuraishShihab in Tafsir Al-Mishbâh. (2). Relevance of teacher characteristics perspective Quraish Shihab inTafsir Al-Mishbâh with characteristics of professional teachers in education Indonesia.Kenis research usedin this research is library research by collecting data and reviewing books that have relevance to thesubject matter. Sources of research data is the book Tafsir Al-Misbâh: Message Impression and Harmonyof the Qur’an. While the secondary book is the books written by M. Quraish Shihab which discuss aboutpemagasi this thesis, as well as other books related to this study. The method used in this research ismaudhû’i method by using content analysis (content analisys). The results of this study are: The characteristicsof perspective teacher M. Quraish Shihab in Tafsir Al-Mishbâh are as follows: The teacher doesthe learning wholeheartedly, conveying all the knowledge that the teacher has to the learners